*This Math quiz is called 'Number Sequences' and it has been written by teachers to help you if you are studying the subject at middle school. Playing educational quizzes is a fabulous way to learn if you are in the 6th, 7th or 8th grade - aged 11 to 14.*

* It costs only $12.50 per month to play this quiz and over 3,500 others that help you with your school work. You can subscribe on the page at Join Us*

A number sequence involves following a pattern. Spotting the pattern is the key! For example, in the sequence 8, 16, 32, 64, ... each number in the sequence can be got from the previous term by multiplying by 2. In this case, the rule is: multiply by 2. The numbers in a sequence are called 'terms': in 5, 10, 15, 20, ... '5' is the first term and '15' is the third term.

If you want to talk about a term without naming it, you call it the n^{th} term. For example, if n = 3, this is the 3^{rd} term. In this quiz you will get some practice in using the rules for sequences.

TIP: To form a sequence from a given rule for the n^{th} term, put n = 1 first, then n = 2, then n = 3 and so on - depending on how many terms you are asked to find. If you are asked to find 5 terms, then you will go as far as n = 5.

1.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = 2n

n

2, 4, 8, 16, ...

3, 6, 9, 12, ...

1, 2, 4, 6, ...

2, 4, 6, 8, ...

2.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = n^{2}

n

1, 4, 9, 16, ...

2, 4, 6, 8, ...

1, 2, 3, 4, ...

1, 8, 27, 64, ...

The terms of the sequence are found by first putting n = 1, then n = 2, then n = 3 and finally n = 4 in the rule for the n^{th} term = n^{2}. As follows:

n = 1 gives 1^{2} = 1

n = 2 gives 2^{2} = 4

n = 3 gives 3^{2} = 9

n = 4 gives 4^{2} = 16

n = 1 gives 1

n = 2 gives 2

n = 3 gives 3

n = 4 gives 4

3.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = 2n + 3

n

1, 7, 9, 13, ...

1, 5, 7, 9, ...

2, 5, 7, 9, ...

5, 7, 9, 11, ...

The terms of the sequence are found by first putting n = 1, then n = 2, then n = 3 and finally n = 4 in the rule for the n^{th} term = 2n + 3. As follows (do the multiplication first THEN the addition):

n = 1 gives 2 × 1 + 3 = 5

n = 2 gives 2 × 2 + 3 = 7

n = 3 gives 2 × 3 + 3 = 9

n = 4 gives 2 × 4 + 3 = 11

n = 1 gives 2 × 1 + 3 = 5

n = 2 gives 2 × 2 + 3 = 7

n = 3 gives 2 × 3 + 3 = 9

n = 4 gives 2 × 4 + 3 = 11

4.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = n^{2} - n

n

0, 3, 8, 15, ...

0, 2, 6, 12, ...

0, 2, 4, 6, 8, ...

1, 3, 5, 7, ...

The terms of the sequence are found by first putting n = 1, then n = 2, then n = 3 and finally n = 4 in the rule for the n^{th} term = n^{2} - n. As follows (do the multiplication first THEN the addition):

n = 1 gives 1^{2} - 1 = 0

n = 2 gives 2^{2} - 2 = 2

n = 3 gives 3^{2} - 3 = 6

n = 4 gives 4^{2} - 4 = 12

n = 1 gives 1

n = 2 gives 2

n = 3 gives 3

n = 4 gives 4

5.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = 4n + 7

n

11, 15, 18, 23, ...

11, 13, 15, 19, ...

11, 15, 19, 23, ...

11, 12, 15, 19, ...

The terms of the sequence are found by first putting n = 1, then n = 2, then n = 3 and finally n = 4 in the rule for the n^{th} term = 4n + 7. As follows (do the multiplication first THEN the addition):

n = 1 gives 4 × 1 + 7 = 11

n = 2 gives 4 × 2 + 7 = 15

n = 3 gives 4 × 3 + 7 = 19

n = 4 gives 4 × 4 + 7 = 23

n = 1 gives 4 × 1 + 7 = 11

n = 2 gives 4 × 2 + 7 = 15

n = 3 gives 4 × 3 + 7 = 19

n = 4 gives 4 × 4 + 7 = 23

6.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = -n + 1

n

0, 1, 2, 3, ...

0, -1, -2, -3, ...

1, 2, 3, 4, ...

1, 3, 5, 7, ...

The terms of the sequence are found by first putting n = 1, then n = 2, then n = 3 and finally n = 4 in the rule for the n^{th} term = -n + 1. As follows:

n = 1 gives -1 + 1 = 0

n = 2 gives -2 + 1 = -1

n = 3 gives -3 + 1 = -2

n = 4 gives -4 + 1 = -3

n = 1 gives -1 + 1 = 0

n = 2 gives -2 + 1 = -1

n = 3 gives -3 + 1 = -2

n = 4 gives -4 + 1 = -3

7.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = -5n

n

-5, -10, -15, -20, ...

5, 10, 15, 20, ...

0, -5, -10, -15, ...

-5, -25, -125, -625, ...

The terms of the sequence are found by first putting n = 1, then n = 2, then n = 3 and finally n = 4 in the rule for the n^{th} term = -5n. As follows:

n = 1 gives -5 × 1 = -5

n = 2 gives -5 × 2 = -10

n = 3 gives -5 × 3 = -15

n = 4 gives -5 × 4 = -20

n = 1 gives -5 × 1 = -5

n = 2 gives -5 × 2 = -10

n = 3 gives -5 × 3 = -15

n = 4 gives -5 × 4 = -20

8.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = 6n

n

6, 12, 18, 24, ...

0, 6, 12, 18, ...

2, 4, 6, 8, ...

1, 6, 12, 18, ...

The terms of the sequence are found by first putting n = 1, then n = 2, then n = 3 and finally n = 4 in the rule for the n^{th} term = 6n. As follows (do the multiplication first THEN the addition):

n = 1 gives 6 × 1 = 6

n = 2 gives 6 × 2 = 12

n = 3 gives 6 × 3 = 18

n = 4 gives 6 × 4 = 24

n = 1 gives 6 × 1 = 6

n = 2 gives 6 × 2 = 12

n = 3 gives 6 × 3 = 18

n = 4 gives 6 × 4 = 24

9.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = 2n - 1

n

1, 3, 5, 9, ...

1, 3, 5, 7, ...

0, 1, 3, 5, ...

1, 5, 15, 45, ...

The terms of the sequence are found by first putting n = 1, then n = 2, then n = 3 and finally n = 4 in the rule for the n^{th} term = 2n -1. As follows (do the multiplication first THEN the subtraction):

n = 1 gives 2 × 1 - 1 = 1

n = 2 gives 2 × 2 - 1 = 3

n = 3 gives 2 × 3 - 1 = 5

n = 4 gives 2 × 4 - 1 = 7

n = 1 gives 2 × 1 - 1 = 1

n = 2 gives 2 × 2 - 1 = 3

n = 3 gives 2 × 3 - 1 = 5

n = 4 gives 2 × 4 - 1 = 7

10.

Which sequence can be formed from the given rule for the n^{th} term?

n^{th} term = 4n - 1

n

5, 7, 11, 15, ...

3, 7, 12, 15, ...

3, 8, 11, 15, ...

3, 7, 11, 15, ...

The terms of the sequence are found by first putting n = 1, then n = 2, then n = 3 and finally n = 4 in the rule for the n^{th} term = 4n - 1. As follows (do the multiplication first THEN the subtraction):

n = 1 gives 4 × 1 - 1 = 3

n = 2 gives 4 × 2 - 1 = 7

n = 3 gives 4 × 3 - 1 = 11

n = 4 gives 4 × 4 - 1 = 15

n = 1 gives 4 × 1 - 1 = 3

n = 2 gives 4 × 2 - 1 = 7

n = 3 gives 4 × 3 - 1 = 11

n = 4 gives 4 × 4 - 1 = 15

^{th}term = 2n. As follows:n = 1 gives 2 × 1 = 2

n = 2 gives 2 × 2 = 4

n = 3 gives 2 × 3 = 6

n = 4 gives 2 × 4 = 8